ANALISIS KEPUASAN PENGGUNA ATAS KUALITAS LAYANAN JARINGAN WIFI DI IST AKPRIND BERDASARKAN KINERJA JARINGAN WIRELESS - Muhammad Yogi Azhar; Rr Yuliana Rachmawati; Joko Triyono (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2018)
IST AKPRIND is a college in yogyakarta city that teaches high education with engineering majors. For the sake of leading college IST AKPRIND already apply today's technology one of them is using wifi network. Users who use the service from IST AKPRIND wifi network not only focus on the price and features offered, but also see the quality of wifi network performance offered by the product. The quality of wifi network services is the totality of features and characteristics of a product or service that depends on its ability to satisfy the stated or implied needs. And quality is an important part of product attributes that affect user satisfaction using wifi network in IST AKPRIND. Testing is done using Axenxe Net Tools, CMD, and Speedtest software. The test is performed on ISTA SLOT A wireless network, ISTA SLOT B, ISTA SLOT C, and WiFi ID. The results showed that the highest average Delay was found on the ISTA SLOT A wireless network, and the lowest was on the WiFi ID wireless network. In the Troughput measurement results, the highest average value is found on the WiFi ID wireless network, and the lowest is in the ISTA SLOT wireless network. IST's IST wireless network ISTA SLOT A, ISTA SLOT B and ISTA SLOT C peformanya are still Lost to the wireless network owned by PT. Telkom is WiFi ID. Only 2 wireless networks owned by IST AKPRIND that can be used by users is ISTA SLOT A, and ISTA SLOT C with ISTA SLOT B can not be used because in down condition. Improvements to improve the performance of wireless networks in Campus 1 IST AKPRIND can be done by adding access point or repeater or brigde, Repair ISTA SLOT B wireless network so that it can reduce the load of ISTA SLOT A wireless network and ISTA SLOT C. wireless network management Bandwidth so that the bandwidth used is more stable than before, created a wireless network user account suapaya users do not seize the bandwidth.